Learning of empathy among first-year medical students - Bulan Kakanita Hermasari; Dian Nugroho (Institute of Advanced Engineering and Science, 2022)
Empathy is one of the core competencies that doctors must possess. Teaching empathy is carried out since students are in undergraduate medical education. One of the learning activities that can be used to improve empathy skills is reflection. Many studies have reported on the empathic abilities of medical students. In addition, there have also been many scientific articles discussing the factors that affect the ability of empathy. However, how medical students learn empathy is still unclear, especially for first-year students who have just been exposed to medical science after graduating from high school. This study aimed to understand how first-year medical students learn empathy. A qualitative study with a phenomenological approach was carried out. We selected randomly, a total of 30 medical student reflection journals were analyzed using content analysis techniques. There are three themes, namely stimulus, process, and effect. Medical students learn empathy driven by internal and external stimuli so that a thinking process occurs through several learning activities. The existence of this stimulus and process influences both the self and the patient/client. The whole process of empathy learning can show how early-year students learn and the factors that influence student empathy learning. This study supports other research that discusses the learning process and factors that affect medical students' empathy. This result can encourage curriculum planners to design appropriate empathy learning for students.